L’administration De La Justice Et La Structure Judiciaire Canadienne - Migneault, Gaétan (Revue de droit de l'Université de Sherbrooke, 2006)
Even though s-s. 92(14) of the Constitution Act, 1867 grants to the provinces a wide jurisdiction over the administration of justice, which includes the constitution and organization of courts, the case law has used s. 96 to limit its scope. This has had the effect of giving constitutional status to the judicial system in existence at the time of Confederation. On the other hand, the Parliament of Canada does not appear to have been subjected to the same constraints, allowing it to confer broad powers to the courts established under its jurisdiction. The only restrictions that seem to have been applied are in the fields of criminal and constitutional law and provincial concerns. Thus, the federal Parliament would be empowered to withdraw from superior courts any other matter within its legislative competence, as long as the jurisdiction is transferred to a s. 101 tribunal. This suggests that s. 96 protects superior courts mostly against provincial measures.